Mário Pinto de Andrade e outro intelectual africano, I Conferência de Escritores Afro-Asiáticos, Taschkent (1958)
Mário Pinto de Andrade e outro intelectual africano, I Conferência de Escritores Afro-Asiáticos, Taschkent.